Health Education Of Anemia In Pregnant Women Using Pocketbook Media On Increasing Knowledge, Attitudes, And Compliance With Fe Tablet Consumption - Wulandari, Anita; Octaviani, Dhita Aulia; Fajrin, Rafika (Postgraduate Program , Poltekkes Kemenkes Semarang, 2023)
The proportion of anemia in pregnancy in Indonesia increased to 48.9%, whereas in Central Java the incidence of anemia in pregnant women was 43.5%. Iron deficiency is often the cause of anemia in pregnant women. Providing information through anemia health education for pregnant women is needed to increase the knowledge, attitudes, and compliance of pregnant women in consuming Fe tablets. The aim was to determine the effect of anemia health education for pregnant women using pocketbooks on increasing knowledge, attitudes, and compliance to the consumption of Fe tablets in Tlogopucang Village, where the village has 43 cases of anemia or 5.6%. This type of research used a pre-experimental design with one group pretest and posttest. The population in this study were pregnant women in the first and third trimesters with a total of 36 respondents. Sampling with total sampling. The instruments used were questionnaires and pocketbooks. Data collection was carried out by pretest and posttest within one day. Statistical test using the Mc Nemar test.The results showed that anemia health education using pocketbooks affected the knowledge, attitudes, and compliance of pregnant women, with the sig score for the prepost test for knowledge, namely 0.008 <0.05, the sig value for the prepost test for attitude, namely 0.000<0.05. As well, the sig value for the prepost test for compliance, namely 0.002<0.05.Pocketbook media can be used as a tool or media to provide health education. It is hoped that health workers and pregnant women can utilize this anemia pocketbook as a source of information about anemia, particularly anemia in pregnancy. Proporsi anemia kehamilan di Indonesia meningkat menjadi 48,9%, di mana Jawa Tengah memiliki kejadian anemia ibu hamil sebesar 43,5%. Defisiensi zat besi sering kali menjadi penyebab kejadian anemia pada ibu hamil. Pemberian informasi melalui pendidikan kesehatan anemia ibu hamil diperlukan untuk meningkatkan pengetahuan, sikap, dan kepatuhan ibu hamil dalam mengonsumsi tablet Fe. Penelitian ini bertujuan untuk mengetahui pengaruh pendidikan kesehatan anemia ibu hamil dengan media buku saku terhadap peningkatan pengetahuan, sikap, dan kepatuhan konsumsi tablet Fe di Desa Tlogopucang, di mana desa tersebut memiliki kasus anemia sebanyak 43 jiwa atau 5,6%. Jenis penelitian ini menggunakan pre eksperimental dengan rancangan one group pretest and posttest. Populasi pada penelitian ini adalah ibu hamil trimester I dan III dengan jumlah 36 responden. Pengambilan sampel dengan total sampling. Instrumen yang digunakan yaitu kuesioner dan buku saku. Pengambilan data dilakukan dengan pretest dan posttest dalam kurun waktu satu hari. Uji statistik menggunakan uji Mc Nemar. Hasil penelitian menunjukkan pendidikan kesehatan anemia dengan media buku saku berpengaruh terhadap pengetahuan, sikap, dan kepatuhan ibu hamil dengan nilai sig skor prepost test pengetahuan yaitu 0,008<0,05, dan nilai sig skor prepost test sikap yaitu 0,000<0,05, serta nilai sig skor prepost test kepatuhan sebesar 0,002<0,05. Media buku saku dapat dimanfaatkan sebagai alat atau media untuk memberikan edukasi kesehatan. Diharapkan tenaga kesehatan dan ibu hamil dapat memanfaatkan media buku saku anemia ini sebagai sumber informasi mengenai anemia, khususnya anemia dalam kehamilan.